2021
DOI: 10.3390/agriculture12010043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extreme Temperature and Soil Water Stress on the Growth and Yield of Soybean (Glycine max (L.) Merrill)

Abstract: Climate change is a major environmental stressor that would adversely affect tropical agriculture, which is largely rain-fed. Associated with climate change is an increasing trend in temperature and decline in rainfall, leading to prolonged and repeated droughts. The purpose of this study was to determine the effect of climate variables such as temperature, relative humidity, vapor pressure deficit (VPD), and soil water on the phenology, biomass, and grain yield of soybean crops. A greenhouse experiment was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
1
8
0
3
Order By: Relevance
“…CCI Showed a positive correlation with yield per plant and negative with oil% and protein%, oil% and protein% showed a negative correlation with LAI, LAD, CCI, and seed yield per plant. Similar results were obtained by Adetokunbo et al [4], Upadhyay et al [5], Mehra et al [6], Weerasekara et al [7], Ogunkanmi et al [8], Soni et al [9], showed similar results .…”
Section: Resultssupporting
confidence: 85%
“…CCI Showed a positive correlation with yield per plant and negative with oil% and protein%, oil% and protein% showed a negative correlation with LAI, LAD, CCI, and seed yield per plant. Similar results were obtained by Adetokunbo et al [4], Upadhyay et al [5], Mehra et al [6], Weerasekara et al [7], Ogunkanmi et al [8], Soni et al [9], showed similar results .…”
Section: Resultssupporting
confidence: 85%
“…The balance of water supply and demand depends on certain temporal and spatial scales and is largely affected by climatic factors and human activities [66,67]. Climate change is expected to affect the water supply and the water demand (especially agricultural demand) under economic and social development in a region [68,69]. The limitation of this paper is that climate change factors are not included in the research framework of agricultural WRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Drought, resulting from low rainfall or high temperature, is an uneven phenomenon that affects plants differently depending on the stage of development when the drought occurs [8]. Wheat is sensitive to high temperatures during most reproductive stages on the other hand, rainfall is often limited and temperatures high during the grain-filling period, and water stress during this period is therefore one of the main production constraints in these environments [9]. Lack of water around an thesis can lead to reduced yields by reducing the number of spikes and spikelets and the fertility of the surviving spikelets, and from an thesis to maturity, particularly if accompanied by high temperatures, leaf ageing is accelerated, the duration and rate of grain filling is reduced, leading to a reduction in average kernel weight and dry matter accumulation [10].…”
Section: Introductionmentioning
confidence: 99%